Mineral in skeletal elements of the terrestrial crustacean Porcellio scaber: SRμCT of function related distribution and changes during the moult cycle. Issue 1 (January 2017) - Ziegler, Andreas; Neues, Frank; Janáček, Jiří; Beckmann, Felix; Epple, Matthias
Abstract: Terrestrial isopods moult first the posterior and then the anterior half of the body, allowing for storage and recycling of CaCO3 . We used synchrotron-radiation microtomography to estimate mineral content within skeletal segments in sequential moulting stages of Porcellio scaber . The results suggest that all examined cuticular segments contribute to storage and recycling, however, to varying extents. The mineral within the hepatopancreas after moult suggests an uptake of mineral from the ingested exuviae. The total maximum loss of mineral was 46% for the anterior and 43% for the posterior cuticle. The time course of resorption of mineral and mineralisation of the new cuticle suggests storage and recycling of mineral in the posterior and anterior cuticle. The mineral in the anterior pereiopods decreases by 25% only. P . scaber has long legs and can run fast; therefore, a less mineralised and thus lightweight cuticle in pereiopods likely serves to lower energy consumption during escape behaviour. Differential demineralisation occurs in the head cuticle, in which the cornea of the complex eyes remains completely mineralised. The partes incisivae of the mandibles are mineralised before the old cuticle is demineralised and shed. Probably, this enables the animal to ingest the old exuviae after each half moult. Graphical abstract: Highlights: The degree of mineralisation varies within skeletal segments according to function. During moult, storage and recycling of mineral varies between skeletal elements. Mineral from the ingested exuviae is taken up via the hepatopancreas. In lenses of the cornea in the complex eyes no resorption of mineral takes place. Parts of the new mandibles become mineralised before the old cuticle is shed.